2000
DOI: 10.1097/00000539-200004000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate Potentiates Morphine Antinociception at the Spinal Level

Abstract: Magnesium sulfate potentiates morphine analgesia when coadministered intrathecally in normal rats, and in an animal model of mechanical allodynia after a surgical incision. These results suggest that intrathecal administration of magnesium sulfate may be a useful adjunct to spinal morphine analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 17 publications
1
43
1
1
Order By: Relevance
“…In another study, by McCarthy and colleagues [22], the addition of magnesium sulfate to morphine in an intrathecal infusion provided better analgesia than morphine alone in normal rats. Kroin et al [23] demonstrated that acute bolus dosing of intrathecal magnesium sulfate produced dose-dependent potentiation of the antinociceptive effect of morphine to noxious thermal stimulation in normal rats and mechanical stimulation at an incisional pain site; these investigators reported that magnesium could potentiate opioid analgesic effects by both central and peripheral mechanisms. In human investigations, Unlugene et al [24] reported that the addition of magnesium or ketamine to morphine for IV patientcontrolled analgesia led to a signifi cantly lower consumption of morphine.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, by McCarthy and colleagues [22], the addition of magnesium sulfate to morphine in an intrathecal infusion provided better analgesia than morphine alone in normal rats. Kroin et al [23] demonstrated that acute bolus dosing of intrathecal magnesium sulfate produced dose-dependent potentiation of the antinociceptive effect of morphine to noxious thermal stimulation in normal rats and mechanical stimulation at an incisional pain site; these investigators reported that magnesium could potentiate opioid analgesic effects by both central and peripheral mechanisms. In human investigations, Unlugene et al [24] reported that the addition of magnesium or ketamine to morphine for IV patientcontrolled analgesia led to a signifi cantly lower consumption of morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous magnesium was used for posttonsillectomy pain in children and reported to have no effect on analgesia [18]. It was demonstrated that the ineffectiveness of magnesium in intravenous applications may be due to its inability to form effective cerebrospinal fluid concentrations because of inadequate penetration through the blood-brain barrier [13]. For this object, Buvanendran et al [20] used magnesium intrathecally and demonstrated that 50 mg intrathecal use of magnesium prolonged analgesia in adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, i.v. magnesium, even high doses, is associated with limited passage across the blood-brain barrier [13].…”
Section: Introductionmentioning
confidence: 99%
“…administered Mg prolonged spinal opioid analgesia both in rats and humans [15,16]. The addition of i.t.…”
Section: Introductionmentioning
confidence: 99%